KANDUNGAN KLOROFIL TUMBUHAN DOMINAN PASCA KEBAKARAN LAHAN GAMBUT DAN PEMANFAATANNYA UNTUK RANCANGAN LKPD BIOLOGI SMA - Putri, Moni Andita; ', Firdaus LN; Wulandari, Sri (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This study aims to determine the effect of fire incident time on chlorophyll content of dominant plants after peat land fires in Rimba Panjang village, Kampar regency. This study was conducted during the months of February to June 2017 using the servei research design. Samples are the dominant strata sapling plant determined based on Important Value Index (IVI) with sampling using purpose random sampling technique based on gradient time of fires (2009, 2013, 2014, 2015, 2016, 2017). The measurement of chlorophyll content was done on the leaves of the three dominant strata sapling plants using Chlorophyll meter SPAD 502, while the physical chemical aspects of the environment were measured using Lux meter to measure light intensity, Thermo hygrometer to measure temperature and humidity, and Soil tester to measure pH and soil moisture. The measurement results dominant chlorophyll content in plants showed that the longer time after the fire the chlorophyll content tends to increase. In addition to the length of time after the fire, environmental factors also affect the chlorophyll content in plants such as, light intensity, soil pH, soil moisture, air temperature, and air humidity. Research result can be utilized for the design of Student WorkSheet of Biology learning in senior high school.Keywords: Chlorophyll Content, Dominant Plants, Post-Fire Peatlands, Student WorkSheet